BPM Suite from Bluespring Software strong web services capabilities and an intuitive user environment. - Barbash, Brian
In the past, business process management has not been a significant area of concern for many corporations. However, with increased regulatory scrutiny facing companies today, the need for formalized definitions, checks and balances and management oversight is a reality.